2021
DOI: 10.21873/anticanres.15474
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemoradiotherapy With Docetaxel, Cisplatin, and 5-Fluorouracil for T3 N0 Glottic Carcinoma Without Vocal Cord Fixation

Abstract: Background/Aim: We retrospectively evaluated the efficacy and toxicity of concurrent chemoradiotherapy (CCRT) with docetaxel, cisplatin, and 5-fluorouracil (TPF) for T3 N0 glottic carcinoma without vocal cord fixation. Patients and Methods: Twenty-five patients underwent TPF-CCRT without elective nodal irradiaion (ENI). After the RT of 40 Gy, five patients (20%) without tumor regression underwent surgery. Others underwent RT with a median total dose of 66 Gy. Results: Of the five patients who underwent surgery… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In T3N0 LC without vocal cord fixation, Toya et al [12] demonstrated that IC provides an excellent pathological response with acceptable toxicities; the problem is that there is toxic accumulation during IC in those patients with a poor response thus retarding radical treatment and worsening patient prognosis. Predicting with high precision response to IC is one of the most interesting fields of research when dealing with LC, since this could guide treatment strategies in locally advanced LC.…”
Section: Introductionmentioning
confidence: 99%
“…In T3N0 LC without vocal cord fixation, Toya et al [12] demonstrated that IC provides an excellent pathological response with acceptable toxicities; the problem is that there is toxic accumulation during IC in those patients with a poor response thus retarding radical treatment and worsening patient prognosis. Predicting with high precision response to IC is one of the most interesting fields of research when dealing with LC, since this could guide treatment strategies in locally advanced LC.…”
Section: Introductionmentioning
confidence: 99%
“…Although total laryngectomy (TL) remains the gold standard for advanced LC, induction chemotherapy (IC) with or without radiotherapy as a standard approach for larynx preservation commonly recommends addressing advanced LC before TL in the current NCCN guidelines (4); it achieves better larynx preservation than immediate surgery without considering overall survival (OS) (5,6). Toya et al (7) reported that IC provides excellent pathological response (PR) with acceptable toxicities in T3N0 glottic carcinoma without vocal cord fixation (7); however, there is a risk of toxic accumulation during IC in patients with poor PR. Thus, it is important to predict the PR with high precision to guide appropriate treatment strategies.…”
Section: Introductionmentioning
confidence: 99%